Fit-To-Go Box ( Healhty Sandwich Box ) / Mohamad Firdaus Mohd Salleh - Mohamad Firdaus, Mohd Salleh (2020)
TWODOTS STOP is a new sandwich on the go shop that serves fresh and healthy sandwiches. Strategically located at the new Esplanad, Eco Grandeur, Puncak Alam, Bandar Puncak Alam, TWODOTS STOP will quickly become the premier healthy food destination in the town, serving locals and students. Keys to Success TWODOTS STOP has identified three keys that will be instrumental in its success. The first is the design and the uniqueness of packing the meal, which will be important, since it’s the era of the technology. The second requirement is that it offers high-quality fresh and healthy food to clearly stand out from the competition. The last key is the need to ensure proper mission. Which is to make people became healthier. TWODOTS STOPS must have targeted marketing campaign to support the opening of the store in order to ensure enough attention. Food TWODOTS offer the community an exciting menu that is a healthy sandwich that suitable for diet people and comes with a green juice. High-fibre bread is a healthy, tasty foundation for a variety of sandwiches. The customers will have the perfect steamed or grilled ingredient such as chicken breast or salmon fillet. Its also contain slices of avocados, tomatoes and fresh salads. The sandwich also comes with the side dish, which is fresh fried potato. Management TWODOTS STOP will be conduct by Mohamad Firdaus, who used to be a motivator and skilful lawyer. Mr. Firdaus worked as a lawyer because of his dream but his passion toward the world is unstoppable. His dream was wanted to make Malaysia as a country that live in a healthy lifestyle.